Unintended Consequences: The impact of migration law and policy - Dickie, Marianne; Gozdecka, Dorota; Reich, Sudrishti (ANU Press, 2016)
This book arose from an inaugural conference on Migration Law and Policy at the ANU College of Law. The conference brought together academics and practitioners from a diverse range of disciplines and practice. The book is based on a selection of the papers and presentations given during that conference. Each explores the unexpected, unwanted and sometimes tragic outcomes of migration law and policy, identifying ambiguities, uncertainties, and omissions affecting both temporary and permanent migrants. Together, the papers present a myriad of perspectives, providing a sense of urgency that focuses on the immediate and political consequences of an Australian migration milieu created without due consideration and exposing the daily reality under the migration program for individuals and for society as a whole.